Extensively Drug-Resistant Typhoid Fever in the United States. (16th November 2021) - Hughes, Michael J; Birhane, Meseret G; Dorough, Layne; Reynolds, Jared L; Caidi, Hayat; Tagg, Kaitlin A; Snyder, Caroline M; Yu, Alexander T; Altman, Shana M; Boyle, Michelle M; Thomas, Deepam; Robbins, Amy E; et al.
Abstract: Cases of extensively drug-resistant (XDR) typhoid fever have been reported in the United States among patients who did not travel internationally. Clinicians should consider if and where the patient traveled when selecting empiric treatment for typhoid fever. XDR typhoid fever should be treated with a carbapenem, azithromycin, or both.